Sistem Penanganan Keluhan Pelanggan Di Hotel Xyz Menggunakan Metode Case Based Reasoning (CBR) - Rayzha Raka Putra; Tacbir Hendro Pudjiantoro; Ade Kania Ningsih (Prosiding SISFOTEK, 2020)
Xyz Hotels is a five star hotel which is a development of a leading hospitality company, Xyz Worldwide. In the service industry like this hotel, one of the factors that influences the level of customer satisfaction at a hotel is the right and fast service in serving complaints of hotel guests. Services at the hotel that are carried out every day require employees to be careful in making improvements to services. The problem that occurs is sometimes hotel employees have not mastered the ability in their fields. Hotel employees should receive training before mastering their respective abilities, the reason is that time is always not available to carry out training, because hotels are always full and crowded every day and have trouble finding time for training, so employees, especially new employees are difficult to serve complaints against hotel guests. Based on these problems, the implementation of Case Based Reasoning (CBR) can be carried out in various fields, one of which is in the service sector to share knowledge and experience from experienced employees to new employees, in order to improve service handling complaints of hotel guests. Using the Case Based Reasoning (CBR) method through four stages, namely retrieve, reuse, revise, and retain. With the aim to solve new problems by adopting the solutions found in previous cases by having problems that are almost the same as the new cases.